2011
DOI: 10.5194/acp-11-11535-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of atmospheric waves on the amounts of polar stratospheric clouds

Abstract: Abstract.A quantitative analysis on the relationship between atmospheric waves and polar stratospheric clouds (PSCs) in the 2008 austral winter and the 2007/2008 boreal winter is made using CALIPSO, COSMIC and Aura MLS observation data and reanalysis data. A longitude-time section of the frequency of PSC occurrence in the Southern Hemisphere indicates that PSC frequency is not regionally uniform and that high PSC frequency regions propagate eastward at different speeds from the background zonal wind. These fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
(60 reference statements)
0
23
1
Order By: Relevance
“…This first survey suggests that formation events appear more frequently in the Southern Hemisphere than in the Northern Hemisphere. This is not consistent with studies showing that there are larger proportions of PSCs due to orographic gravity waves in the Arctic than in the Antarctic (Kohma and Sato, 2011;. However, our findings might be biased due to the more stable atmospheric conditions in the Southern Hemisphere, which ease the identifica- Figure 13.…”
Section: Datecontrasting
confidence: 80%
See 1 more Smart Citation
“…This first survey suggests that formation events appear more frequently in the Southern Hemisphere than in the Northern Hemisphere. This is not consistent with studies showing that there are larger proportions of PSCs due to orographic gravity waves in the Arctic than in the Antarctic (Kohma and Sato, 2011;. However, our findings might be biased due to the more stable atmospheric conditions in the Southern Hemisphere, which ease the identifica- Figure 13.…”
Section: Datecontrasting
confidence: 80%
“…Previous studies on PSC formation used mesoscale model output (Höpfner et al, 2006a;Noel and Pitts, 2012;Orr et al, 2015) or global positioning system radio occultation observations (Kohma and Sato, 2011;Alexander et al, 2011 as a source of information on gravity waves. The use of Atmospheric Infrared Sounder (AIRS) observations for that purpose was first explored by Eckermann et al (2009) and Lambert et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that PSCs are sometimes observed in association with anticyclonic PV anomalies near the tropopause (Teitelbaum et al, 2001;Kohma and Sato, 2011). Figure 6 shows the probability of the simultaneous occurrence of PSCs and UCs at 70-75 • S in June through September of 2007-2011 as a function of PV anomalies from the zonal mean of 300 K (∼ 8 km) and 550 K (∼ 23 km) isentropic surfaces.…”
Section: Role Of Tropospheric Anticyclones In Simultaneous Appearancementioning
confidence: 99%
“…Dörnbrank and Leutbecher (2001) showed that temperatures low enough to enable the formation of ice PSCs are controlled by mesoscale temperature fluctuations due to mountain waves in the Arctic, while NAT formation is significantly controlled by the synopticscale temperature fluctuations. Kohma and Sato (2011) quantified the contribution of each type of waves to the areal extent of PSCs in both hemispheres using a temperature threshold based on temperatures from reanalysis data and GPS radio occultation observations and mixing ratios of HNO 3 and H 2 O from microwave limb sounder observations. They showed that planetary-scale temperature perturbations have a great contribution to areal extent of PSCs in the latitude range of 55-70 • S while the contribution of synoptic-scale perturbation is large only around an altitude of 12 km.…”
Section: Kohma and K Sato: Polar Stratospheric Clouds And Upper-tmentioning
confidence: 99%
See 1 more Smart Citation